Asymptomatic Ruptured Thymic Branchial Cyst in a Beagle Bitch - Successful Surgical Resection - Kim, Minkyung; Yoon, Eun-Chae; Kim, Young-Hwan; Hyun, Jae-Eun; Cho, Jae-Hyeon (Acta Scientiae Veterinariae, 2025)
Background: A thymic cyst is an extremely rare nontumorous thymic disease in dogs. The cyst may appear in the neck or thoracic regions and can cause clinical signs such as dyspnea and pleural effusion. Despite its benign behavior, it may occasionally lead to severe complications such as hemothorax if the cyst ruptures. Additionally, thymic cysts have the potential to compress vascular structures, cause pleural effusion, and, in rare instances, coexist with thymomas or progress to carcinoma, often necessitating surgical intervention for treatment. Imaging and cytologic evaluations present diagnostic limitations; therefore, histopathological examination is required for a definitive diagnosis. The objective of this study is to describe the clinical characteristics of dogs with ruptured thymic cysts, as well as to discuss the diagnostic and therapeutic approaches. Case: A 13-year-old spayed Beagle bitch, weighing approximately 20 kg, was presented for a medical checkup. The physical examination yielded no significant findings, and complete blood count, serum chemistry, and electrolytes showed no significant findings. However, thoracic imaging revealed an unexpected anterior mediastinal mass. Subsequent computed tomography confirmed a 55.9 × 68.5 × 54.6 mm partially fluid-filled mass adjacent to the heart but without the displacement of nearby structures or pleural effusion. Despite the absence of symptoms, surgical intervention was considered due to possible malignancy and to prevent further problems. Median sternotomy was performed for mass removal. The mass was adherent to the cranial vena cava, and we carefully extracted it while minimizing bleeding and preserving the integrity of adjacent organs. The sternum was secured using stainless steel wire, and the muscle, subcutaneous tissue, and skin layers were closed with conventional suturing methods. The removed mass had a solid appearance with some protrusions and a firm texture. Upon excision, it revealed a large cavity filled with serosanguineous fluid and several smaller cysts. Post surgery, the dog recovered well and was discharged on Day 10 without complications. Histopathological evaluation revealed thymic cysts with a central area of necrosis and hemorrhage, resulting from cyst rupture. A limited amount of thymic tissue, composed of thymic epithelial cells and small lymphocytes, was observed surrounding the cyst; however, no evidence of malignancy was identified. The dog lived for another three years without any thoracic issues before dying due to systemic disease. Notably, there was no recurrence of the thoracic condition, confirming the successful resolution of the initial concern. Discussion: The present study demonstrated the successful surgical treatment of an incidentally discovered ruptured thymic cyst in a Beagle bitch. Although thymic cysts in dogs are typically nonneoplastic, preoperative imaging often has limitations in diagnosis, and co-occurrence with neoplasms has also been reported. Furthermore, their rupture often leads to inflammation and hemorrhage, which necessitates surgical resection. The patient in this study was asymptomatic despite the rupture of the thymic cyst. The dog recovered without complications following cyst removal, and no recurrence was observed. Previously reported cases of thymic cysts in dogs have frequently documented serious complications such as pyothorax, hemothorax, and sepsis, as well as recurrence and progression to neoplasia. Based on the favorable outcome observed in this case, we recommend early surgical intervention prior to the onset of clinical symptoms of thymic cysts. Keywords: dog, median sternotomy, thoracic mass, thymic cyst, thymoma.